Bagaimana Tingkat Kepuasan Ibu Hamil pada Pelayanan Antenatal? Hasil Penerapan Model Pelayanan Antenatal Kontinu - Baiq Iin Rumintang (Jurnal LINK, 2015)
The research purpose is to measure the level of satisfaction between women who undergo routine antenatal care model and women who undergo continuous model of antenatal care. This research is analytic with true experimental design with pretest-posttest control group design. In the pre-treatment analysis, 16% of the control group and 40% of the intervention group expressed great satisfaction (p =0.013). In the analysis of post-treatment, 11% of the controls group and 60% of the intervention group expressed great satisfaction (p =0.000). Satisfaction dimensional analysis results each group obtained in the intervention group dimensions of technical quality, personal management, communication, time with midwives and access p 0.05. Providing quality information on both there is no difference (p 0.05) except for the category preparations for complications (p =0.021). The conclusion is: there is a high level of satisfaction in pregnant women who undergo continuous model of antenatal care compared to the routine antenatal care models and there are no differences in the quality of the provision of informations of those women.